ETHNICITY AND THE SHARE OF SOCIAL HOUSING FOR OLDER PEOPLE IN THE METROPOLITAN WEST MIDLANDS - Dixon, Andrew (Sociologija. Mintis ir veiksmas, 2015)
This paper draws on research on ethnicity and equity in the uptake of housing for older people provided in the (non-commercial) social sector, and on data collected to inform the case for sensitivity in the planning and delivery of housing and related services for minority ethnic older people. The study area comprised five metropolitan districts in the West Midlands – Birmingham, Dudley, Sandwell, Walsall and Wolverhampton. The research focused on older people from the White British, White Irish, Black Caribbean, Pakistani and Indian communities. In this paper an estimate of minority ethnic representation in municipal housing for older people relative to the incidence of White British occupancy is presented. Estimates are prepared with respect to the districts of Birmingham, Sandwell and Wolverhampton. Additionally, an interpretation of the estimated representation patterns is sketched out, drawing on the reported responses of people in later life from White Irish, Black Caribbean, Pakistani and Indian communities; respondents were asked about what they know of housing for older people provided by social sector landlords, and what they want from housing as they become older.
Keywords: housing for older people; estimated representation; differential use; minority ethnic people in later life